Role of Health Economic Data in Policy Making and Reimbursement of New Medical Technologies - Tetsuji Yamada; Mihajlo (Michael) Jakovljevic (Frontiers Media SA, 2017)
This Research Topic was focused on provision of novel medical technologies worldwide keeping in mind financial sustainability challenge. An exemplary area certainly are oncology pharmaceuticals where prices have increased 10-fold in recent years leading to concerns on affordability. The objective of this collection of studies was to reveal some of the hidden underlying causes of unequal access to the medicines. Another core issue is the growing proportion of out-of-pocket health spending in many world regions. In line with the joint efforts of the editors and authors we received an exceptionally high response worldwide. This E-Book attracted a total of 37 self-standing research submissions out of which 32 ultimately passed external peer review and got published. Base affiliations of the authors spread across academia, pharmaceutical and medical device industry, governmental authorities and clinical medicine. Their home institutions were situated in fifteen different countries inclusive of Japan, Israel, Russia, USA, Germany, Italy, Netherlands, Austria, Spain, Malta, Serbia, Poland, Bulgaria, Hungary and Malaysia. We frankly believe that authors succeeded to cover important literature gaps referring to these world regions. We solicit global professional audience to put our efforts to the test and read this contribution to the health economics literature.
English
Keywords: Decision Making; health technology assessment; Health Economics; cost; health policy; Health expenditure; Resource Allocation; health investment; reimbursement; medical technology; Emerging Markets